Neuroprotective, eco-friendly iron oxide nanoparticles to alleviate Parkinson’s disease symptoms and improve nursing care - Chen, Shuangyan; Jiang, Ting (Frontiers in Neuroscience, 2026)
BackgroundParkinson’s disease (PD) involves motor impairment and neurochemical changes, necessitating neuroprotective agents to enhance nursing care outcomes.MethodsIron oxide nanoparticles (IONPs) were biosynthesized via green chemistry and characterized by TEM, UV-Vis, photoluminescence, XRD, and VSM. Antioxidant activity used DPPH assay; biocompatibility involved MTT and hemolysis assays. Efficacy was tested in an MPTP-induced mouse model of PD, assessing motor function, antioxidant capacity, and dopaminergic neuron protection.ResultsIONPs exhibited spherical morphology (39.0 ± 11.3 nm), zeta potential of −13 mV, and saturation magnetization of 42.32 emu/g. They showed concentration-dependent DPPH scavenging and no significant cytotoxicity or hemolysis up to 10 µg/mL. In vitro, IONPs improved motor performance, boosted antioxidants, and reduced apoptosis in dopamine neurons.ConclusionBiosynthesized IONPs offer promise as a complementary PD therapy by mitigating motor deficits and neurochemical damage.